Hubungan Tingkat Stres Dengan Perilaku Berpacaran Pada Remaja Di SMA X Cawang Jakarta Timur - Diah Ratnawati; Ismi Dyah Astari (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2019)
Stress is the psychic reaction of the body that arising from the presence of internal and external pressure. Date is an approach period between both opposite sex individuals, which is signed by personal introduction of their strength and weaknesses. Adolescent can not control themselves from pressure will trigger appear stress that can change behavior be like relationship. This study will conducted to see correlation between stress level by behaving dating in Senior High School X. Research was conducted to adolscents boys and girls with criteria ever or while correlation and age between 15-18 years. As the subject research will be sample is 236 students with distribution of male respondents 116 people and female respondents 120 people. Stress level variable was measured by used scale to standard anxiety and stress scale (DASS). While the measuring behavior to correlation of the researcher make a questionnaire with especially do it test the validity before the research. Kind of research was used quantitative research with method approach cross sectional and took sample do with techniq stratified random sampling. Based on research results found that the there is a correlation between stress level with dating behavior inadolescents Senior High School X Cawang. The results of this study is expected adolescents can take a positive value in dating behavior.